Reconceptualising postgraduate taught student experience through the lens of emotions and well-being: Moving from explanatory methodology to revelatory. (2023) - White, Wendee; Ingram, Richard
Highlights: Emotion drives postgraduate taught (PGT) student experience, underpinning wellbeing and learner success. Emotion is a multicomponent process with functional and consequential implications to student experience. A new methodological approach supports exploring the complexity of PGT student emotion. Understanding emotion can contribute to proactive approaches that inform student wellbeing and experience. Abstract: This study introduces a methodological approach for exploring taught postgraduate (PGT) student experience as a relationship with emotion and wellbeing. We examine the anatomy of PGT student emotions at one UK university and explore their functional and consequential role in student experience. Findings suggest PGT student experience is defined by a complex array of emotions that interact closely with appraisal, motivation, and behaviour. They have deleterious or beneficial impact on core dimensions of learning and wellbeing including engagement, cognitive flexibility, and social connectedness. Our methodological approach provides an avenue for exploring this complexity through a multi-level and revelatory examination of emotions, from which it is possible to develop proactive approaches to student wellbeing through improved emotion awareness, competencies, and control.